Islam: the spirit of creativity - Badi, Jamal Ahmed Bashier (IIIT, 2019)
In order to make the sourcebook "Creative Thinking in Islam: Concepts and Issues" more user-friendly, various methods and schemes were utilised. The main ideas of the textbook are related to everyday student life in an effort to aid student visualisation, and in a bid to make theoretical suggestions metamorphose into practical solutions.